Immersion in open-world games based on Grounded theory – A case study of Genshin Impact - Wang, Yang (Transactions on Computer Science and Intelligent Systems Research, 2024)
In recent years, with the expansion of the game market and the rapid growth of game users, the game market has great potential. At the same time, open world games are loved by the vast majority of users. [Purpose/Significance] Explore the factors that affect the immersion of players in open world games, drive the improvement of the quality of open world games, help improve the industrial ecology, and achieve richer functional values. [Research design/Methods] Taking the open world adventure role-playing game "Genshin Impact" as a case study, semi-structured interview was used to obtain first-hand interview data, and coded research was conducted using grounded theory. Through several processes such as open coding, spindle coding, selective coding and theoretical saturation testing, the corresponding theoretical model is finally formed. [Conclusion/Finding] The results show that the basic feature of immersion performance is concentration. The two factors, the in-game condition and the out-of-game condition, together constitute the pre-factors that produce immersion. After entering the state of immersion, the main performance is to produce tension and emotional resonance. [Innovation/Value] builds a theoretical model for the generation of immersion in open world games, which lays a theoretical foundation for future theoretical model testing and empirical research.